Outcomes of disease prevention and management interventions in food pantries and food banks: protocol for a scoping review. Issue 10 (5th October 2017) - Long, Christopher R; Rowland, Brett; Steelman, Susan C; McElfish, Pearl A
Abstract : Introduction: Food insecurity is a difficulty faced in many households. During periods of food insecurity, households often seek food supplied by food pantries and food banks. Food insecurity has been associated with increased risk for several health conditions. For this reason, food pantries and food banks may have great promise as intervention sites, and health researchers have begun targeting food pantries and food banks as sites for disease prevention or management interventions. The aim of the scoping review is to examine disease prevention or management interventions implemented in food pantries and food banks. Methods and analysis: Relevant electronic databases (eg, MEDLINE, Cumulative Index to Nursing and Allied Health Literature-CINAHL Complete, Science Citation Index, Cochrane Database of Systematic Reviews) will be searched for articles with a publication date of 1997 or later using Medical Subject Headings and key terms, including food aid, food banks, food pantries, food shelves, hunger, food insecurity and related concepts. For each de-duplicated study record identified by the search strategy, two reviewers will independently assess whether the study meets eligibility criteria (eg, related to intervention type, context). The reviewers will examine studies' titles, abstracts and full text, comparing eligibility decisions to address any discrepancies. For each eligible study, data extraction will be executed by two reviewers independently, comparing extracted data to address any discrepancies. Extracted data will be synthesised and reported in a narrative review assessing the coverage and gaps in existing literature related to disease prevention and management interventions implemented in food pantries. Ethics and dissemination: The review's results will be useful to healthcare practitioners who work with food-insecure populations, healthcare researchers and food pantry or food bank personnel. The results of this scoping review will be submitted for publication to a peer-reviewed journal, and the authors will share the findings with food pantry and food bank stakeholder groups with whom they work.